Empirical survey on business models of kindergarten farms - Biancamaria Torquati; Costanza Tancini; Chiara Paffarini; Roberta Illuminati (Agricultural and Food Economics, 2015)
The paper presents a study of a new social farming initiative: kindergarten farms. The paper emphasizes the value of potential synergies between the agricultural and the educational service. The two case studies analyzed are high-quality Italian kindergartens supported by a Marche Region project to foster employment in rural areas and improve the quality of life. The entrepreneurial models were investigated using the Business Model Canvas (BMC), which enabled us to examine the economic results of the kindergarten farm, the importance of the farm location, and the role of public decision-makers. The results show that the kindergarten farms offer a new way to achieve economic diversification, to supplement the incomes of rural people, to support exchange between generations, and to reduce the public cost of social services.
Keywords: Q12; O18; I20; 330; Social farming; Kindergarten farm; Business Model Canvas